Understanding Involvement in Terrorism and Violent Extremism: Theoretical Integration through the ABC Model - Khalil, James (Terrorism and political violence, 2024)
Scholars seeking to understand why individuals become involved in terrorism and violent extremism rely on a multitude of theoretical frameworks. While these are commonly interpreted as being in antagonistic opposition, the core premise of this article is that further advances in our understanding of this violence are contingent upon us treating them as complementary. Limiting ourselves to three frameworks that are perhaps most in tension, we survey the core premises of the rational choice perspective (RCP), the social identity perspective (SIP), and the ideological perspective (IP), identifying opportunities for theoretical integration. We argue that individuals are driven to involvement in this violence by both personal rewards and collective objectives, making both the RCP and SIP frameworks indispensable. We also conclude that SIP interpretations are incomplete without the IP, as ideologies play a pivotal role in constructing and amplifying ingroup and outgroup identities. The RCP is also deficient in the absence of the IP as many rewards that motivate involvement can only be understood through reference to the ideational context in which they are conferred. Systematic recognition and application of this theoretical complementarity is facilitated, we further argue, by the Attitudes-Behaviors Corrective (ABC) Model, which we apply as a heuristic device throughout the article.